Empathy in Portuguese medical students: a cross-sectional study using the Jefferson Scale of Physician Empathy - Pedro António Vilela Teixeira (2022)
Background: Empathy is a multi-factorial concept that plays a vital role in a patient centered health care. Therefore, medical schools should promote strategies to improve students' empathy profiles. Objectives: To analyze the performance on the Jefferson Scale of Physician Empathy of first- and second-year medical undergraduates, and study its association with personal and academic characteristics of the students. Methods: First and second year students from Faculdade de Medicina da Universidade do Porto (FMUP) completed Jefferson Scale of Physician Empathy Student Portuguese Version (JSPE-spv) evaluating each both total (from 20 to 140) and parcial score for each component:"perspective taking", "compassionate care", and "standing in the patient's shoes". Students' performance on JSPE-spv was compared according to multiple variables, including gender, admission grade and previous high school characteristics, working student status and academic performance. Results: From a total of 685 students on the first and secon year, 539 (78,69%) agreed to participate, 70,10% were female, 38,03% were in the first year, 45,27% second year, and 16,70% of the students were repeating a phisiology course from the previous year. Female students exhibited higher scores in JSPE when compared to males (94,15 ± 10,45 vs 88,32 ±13,31 p<0,001). Students that were repeating a physiology course had higher total empathy scores when compared to students enrolling for the first time (94,27 ± 9,94 vs 91,93 ±12,05 p=0,035). A positive correlation was found between the average classification of courses on the first year of medical school and empathy scores (r=0,142, p=0,015). No statistically significant differences in empathy scores were observed between first and second year students (91,68 ± 12,25 vs 92,86 ±11,31 p=0,257), public versus private high school students (92,48 ± 11,48 vs 92,28 ±12,05 p=0,846), or full time students versus working students (94,34 ± 12,52 vs 92,28 ±11,62 p=0,312). No correlation was observed between total JSPE scores and high school final grade (admission grade) (r=0,034,p=0,438), and classification on the Musculoskeletal Morphophysiology (r= 0,037, p=0,582) or, Cardiovascular Morphophysiology (r= 0,112, p=0,061). Conclusions: The total JSPE score did not differ between first and second grade medical students. Academic performance during the first year is positively corretated with empathy scores. Those who were not approved and were repeating a phisiolgy course demonstrated superior empathy scores. Clinical experience and personal characteristics are important factors in physician empathy. A reflection should be made on the focus of developing empathy values among medical students from the beginning of their medical education.